RESISTANCE OF SOME COWPEA LINES TO BROWN BLOTCH DISEASE - OBISESAN, I. O.; ONESIROSAN, P. T.; ADEBITAN, S. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Sixty-four lines of cowpea (Vigna unquiculata L, Walp sub sp. unquiculata) were screened for resistance to brown blotch disease both in the greenhouse and in the field. Field screening was conducted during 4 growing seasons. Results or both greenhouse and field corroborated each other as no line identified as resistant in greenhouse was susceptible in the field or vice versa. Throughout the study, Crimson. Hope, TVx3236, TVu 1896 AG and H 144-1 were consistently resistant while Ife Brown, Ife BPC, A44/2 were susceptible.